The population, protein profile and ultrastructure of Ascaridia galli in chicken treated using Areca catechu crude aqueous extract - Mubarokah, W. W.; Nurcahyo, W.; Prastowo, J.; Kurniasih, K. (Journal of the Indonesian Tropical Animal Agriculture, 2019)
The study aimed at investigating the population, the protein profile and the ultrastructure of adult worms in the intestine of domestic chicken treated using Areca catechu crude aqueous extract. Fifty domestic female chickens of 6 weeks of age were assigned to 5 groups. Group A (negative control) was not given any treatment and any drug. Groups B, C and D were given the treatment at the doses of 26 mg/mL, 53 mg/mL and 79 mg/mL, respectively. Group E (positive control) was given Pyrantel®. Necropsy was conducted to all of the chickens 14 days after the treatment. Adult worms were collected and counted. The worms used in Sodium Dodecyl Sulfate Polyacrylamide Gel Electrophoresis (SDS-PAGE) and Scanning Electron Microscopy (SEM) were those collected from the jejunum of the chickens in the groups A, B and C. The biggest number of the worms was found in the jejunum. The results of electrophoresis showed that the dose 53 mg/mL gave fewer protein bands than the negative control (21:12 ratio), while the results of the SEM showed that there was cuticle damage and anterior labia abrasion at the dose of 53 mg/mL. The Areca catechu crude aqueous extract showed anthelmintic activity potential by reducing the number of the adult worms, lowering their protein profile and damaging the A. galli worms in the intestine.